Pengembangan modul pembelajaran konstruktivistik kontekstual berbantuan komputer dalam matadiklat pemesinan - Sudji Munadi (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2011)
DEVELOPING OF COMPUTER ASSISTED CONTEXTUAL CONSTRUCTIVE LEARNING MODULE IN THE MACHINE TRAININGThis research was aimed at investigating constructivist learning model for machining process. Interactive Computerised Module of constructivist teaching principle has been developed at the first year of research. This further research was aimed at implemention of the module and its effectiveness. This research was carried out by means of Research and Development. Data was analysed descriptively. The research investigated, that: module have satisfied feasibility both in theoretical and empirical aspects. There are three roles of module: (1) as media, (2) as supporting media in practice, (3) as interactive and individual learning. The implementation of module into teaching and learning should not in uniform manner within different teachers and facitlities for vocational schools.